Anti-human trafficking laws and their implementation in Malaysia - Zuraini binti Ab Hamid (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
Human trafficking is a transnational organised crime which has threatened all regions around the world. There are significant problems with the Malaysia legal framework and its enforcement in dealing with the crime which contributes to the country's downgrade to Tier 3 in 2014 from its previous ranking as a Tier 2 Watch List country, in Trafficking in Persons reports 2011 to 2013, provided by the US Department of State. Therefore, the principal objective of this thesis is to examine the Malaysian legal framework on human trafficking and its enforcement by government bodies. The analysis is valuable in finding the reasons of Malaysia's inefficiencies to combat the crime. This study indicates that the inefficiencies are rooted from the obstacles faced by the enforcement bodies in combatting the crime due to their lack of manpower, experts, and basic facilities. The methodology utilised is fieldwork research which data was gathered from government enforcement and legal officers, together with published printed sources. All research data are supported by statistical data and cases obtained from the authority and reliable sources. This thesis concludes with suggestions and recommendations for Malaysia's improvement, including through law reformation and effective efforts to overcome human trafficking. This thesis will benefit Malaysia in determining the root cause of its inefficiencies in combatting human trafficking, thus enhancing the country's position in the Trafficking in Persons report.